Household Resilience to Power Outages - Kock, Tobias; Quesada, Daniel (My University, 2026)
The purpose of this study is to investigate the resilience capabilities of house holds in case of power shortages/outages and their ability to adapt to these situations and to find out how long a villa district can maintain power with basic living conditions from an electric power supply point of view. By using Matlab, an artificial test environment was created in order to simulate how much power consumption behavior affects the overall consumption, specifically focusing on the heat pump and the electrical water heater. Using data from monthly generated solar power in Stockholm Sweden and the power storage capabilities of electric vehicles in order to prolong the resilience time of the households in these situations. The results of implementing the combination of solar panels and vehicle to grid technologies has shown that with some changes to daily life power consumption, the residential area can potentially provide sufficient energy locally for up to 65% of the year without grid support, given weather conditions do not stay dark for longer periods of time.